Knowledge promotion and upgrading the quality of pickled bamboo shoots to ensure hygiene in pickled bamboo shoot occupation group Ban Kaeng Subdistrict, Mueang Sa-Kaeo District Sa-Kaeo Province - Kraitip, Bentanasiwarat; Kaewpuang, Teadkait (Journal of Local Governance and Innovation, 2022)
Promoting and enhancing the quality of pickled bamboo shoots for hygiene of occupation group of pickled bamboo shoots in Ba- Kaeng Subdistrict, Mueang Sa-Kaeo District Sa-Kaeo Province, aims of this research was to solve problems and improve the quality of pickled bamboo shoots which was a processed local product and would be able to lead to standard certification in future. Promoted knowledge process was to solve the problem of hygienic pickled bamboo shoot production process. The process of cleaning salt that was a key ingredient, by salt crystallization method makes the salt purity and clean. Moreover, the were understood the benefits of pickled bamboo shoots and caution in eating bamboo shoots. Bamboo shoot processing was kept clean, maintain hygiene, the environment and reduction of cyanide from bark and pulp of bamboo shoots. The researcher/ The target groups have conveyed knowledge to the local people. The results of knowledge transfer showed that the occupation group had knowledge and understanding in the process of processing pickled bamboo shoots, produce hygienic salt by themselves and could be used as a key ingredient in hygienic pickled bamboo shoot production. In addition, the understanding and awareness in solve the problem of cyanide in the bark and pulp of bamboo shoots was used soaking in water method to dissolve the cyanide from the bark before discarding. This method was reduced the toxins from the bamboo shoots before discarded or burned as fuel. The boiling for 45 - 60 minutes can destroy the cyanide in the bamboo shoots before eating or cooking.